(untitled) (Journal of Civil Engineering Researchers, 2025)
Understanding the dynamic behavior of soil layers under seismic loading is pivotal for accurate seismic design and risk assessment. This study conducts a two-dimensional equivalent linear site response analysis using the Scaled Boundary Finite Element Method with Rayleigh damping to enhanced modeling accuracy. SBFEM combines the advantages of finite and boundary element methods, offering high efficiency in simulating wave propagation and stress concentrations in semi-infinite domains. A MATLAB implementation of the method was validated against previous studies, confirming consistent accuracy across various soil profiles and seismic scenarios. The method demonstrates convergence, accuracy, and stability, requiring fewer elements due to boundary-only discretization. This reduces both computational cost and time while accurately modeling the infinite domain condition. The findings highlight the method’s effectiveness for site response analysis under diverse seismic inputs and layered soil configurations, combining the equivalent linear method with SBFEM as a robust and practical tool for dynamic geotechnical applications.